2006
DOI: 10.1108/00483480610656685
|View full text |Cite
|
Sign up to set email alerts
|

Career advancement of hotel managers since graduation: a comparative study

Abstract: PurposeTo investigate the factors predicting the career progression of hotel managers working in international hotel chains in Ireland, Europe and Asia.Design/methodology/approachThe study uses a cross‐sectional questionnaire design consisting of 337 respondents. It investigates individual‐ and organisational‐level factors that potentially explain the career progression of hotel managers.FindingsThe study reveals significant differences in managerial progression in the three sub‐samples. A multiplicity of fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 96 publications
6
60
2
2
Order By: Relevance
“…The current study supported the findings of Garavan et al (2006), who found that limited career development undermined the positive form of stress. Lo & Lamm (2005) also found that high levels of distress in the hotel sector increased turnover rates.…”
Section: May 108supporting
confidence: 80%
“…The current study supported the findings of Garavan et al (2006), who found that limited career development undermined the positive form of stress. Lo & Lamm (2005) also found that high levels of distress in the hotel sector increased turnover rates.…”
Section: May 108supporting
confidence: 80%
“…The first one is that of Glaser and Strauss, [8] , the second one is that of Strauss and Corbin, [21] and the third one is that of Chamaz , [5]. According to Glaser, the researcher under the grounded theory approach should not do a literature review first since it will influence the theory building process.…”
Section: Research Methodology Qualitative Research Methodologymentioning
confidence: 99%
“…Managers having management qualifications, for example, achieve general management positions more quickly than those without such qualifications. On the other hand, the importance of food and beverage knowledge and knowledge in other technical areas is still important for getting general hotel management positions, Garavan et al, [8], Ladkin and Jawaheer, [12]. Many hospitality graduates take first line management or supervisory positions in order to get the needed knowledge and experience and with time, they hope to develop their career either within the particular hotel or outside it, Ladkin, [12] .…”
Section: Management Development Within the Tourism Sectormentioning
confidence: 99%
See 2 more Smart Citations